Carbapenemase activity detection by matrix-assisted laser desorption ionization-time of flight mass spectrometry - Hrabák, Jaroslav; Walková, Radka; Studentová, Vendula; Chudácková, Eva; Bergerová, Tamara (Journal of clinical microbiology, 2011)
Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry is used for the determination of molecular weights of different chemical compounds. We describe here the use of MALDI-TOF mass spectrometry to detect a carbapenem antibiotic, meropenem, and its degradation products. Buffered meropenem solution (0.1 mM Tris-HCl, pH 6.8) was mixed with an overnight culture of bacteria. After 3-h incubation, the reaction mixture was centrifuged, and the supernatant was analyzed by MALDI-TOF mass spectrometry. The presence or absence of peaks representing meropenem and its sodium salts was crucial. The average turnaround time of this test, considering the use of overnight culture, is 4 h. We validated this method for the detection of resistance to carbapenems in Enterobacteriaceae and Pseudomonas aeruginosa mediated by carbapenemase production. A total of 124 strains, including 30 carbapenemase-producing strains, were used in the study. The sensitivity of this method is 96.67%, with a specificity of 97.87%. Our results demonstrate the ability of this method to routinely detect carbapenemases in Enterobacteriaceae and Pseudomonas spp. in laboratories. This assay is comparable with a labor-intensive imipenem-hydrolyzing spectrophotometric assay that is a reference method for the detection of carbapenemase. As demonstrated here, MALDI-TOF mass spectrometry may be used in microbiological laboratories not only for microbial identification but also for other applications, such as studies of mechanisms of antibiotic resistance.
Keywords: meropenem; Enterobacteriaceae; bakteriální proteiny; senzitivita a specificita; thienamyciny; antibakteriální látky; spektrometrie hmotnostní - ionizace laserem za účasti matrice; beta-Lactamases; Thienamycins; lidé; Pseudomonas aeruginosa; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; beta-laktamasy; Anti-Bacterial Agents; Bacterial Proteins; Humans; Meropenem; Sensitivity and Specificity